2022
DOI: 10.1029/2022gc010514
|View full text |Cite
|
Sign up to set email alerts
|

NW Pacific‐Panthalassa Intra‐Oceanic Subduction During Mesozoic Times From Mantle Convection and Geoid Models

Abstract: The plate tectonic history of the Pacific Ocean and its predecessor ocean, Panthalassa, are the most challenging regions on Earth to reconstruct within the Mesozoic and Cenozoic eras (Müller et al., 2016). The Pacific Ocean currently covers >25% of the present Earth surface and is the largest ocean basin on Earth; however, the Pacific-Panthalassa oceanic realm was even larger during the late Mesozoic, when it covered ∼45% of Earth and 65% of oceanic areas (Torsvik et al., 2019). Much of the Pacific-Panthalassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Deeper slabs imaged within the mantle at depths below ~2300 km likely record subduction before the mid-Cretaceous. Although their interpretation is less straightforward, forward geodynamic models and tomographic studies suggest that backarc basins and intra-oceanic subduction zones formed offshore of Japan prior to 85 or 100 Ma (van der Meer 2012; Lin et al 2022). Such ideas are supported by geological studies of subduction complexes in Hokkaido, Japan (Ueda and Miyashita 2005).…”
Section: Insights From Mantle Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Deeper slabs imaged within the mantle at depths below ~2300 km likely record subduction before the mid-Cretaceous. Although their interpretation is less straightforward, forward geodynamic models and tomographic studies suggest that backarc basins and intra-oceanic subduction zones formed offshore of Japan prior to 85 or 100 Ma (van der Meer 2012; Lin et al 2022). Such ideas are supported by geological studies of subduction complexes in Hokkaido, Japan (Ueda and Miyashita 2005).…”
Section: Insights From Mantle Tomographymentioning
confidence: 99%
“…The Izanagi slabs at 1300 to 2000 km depths under Japan (Fig. 3) account for westward subduction under Japan from the early Cenozoic ~50 Ma to the mid-Cretaceous ~100 Ma (Wu et al 2022b;Lin et al 2022), or Jurassic (Seton et al 2015). Deeper slabs imaged within the mantle at depths below ~2300 km likely record subduction before the mid-Cretaceous.…”
Section: Insights From Mantle Tomographymentioning
confidence: 99%
“…kinematically constrained by reconstructed plate motions and aiming to resemble Earth-like features (e.g., Bull et al, 2014;Coltice & Shephard, 2018;Faccenna et al, 2013;Flament et al, 2022;Li et al, 2023;Lin et al, 2022) configurational entropy may serve as a means to quantify and map the degree of mixing, and hence to determine average cell composition, on a local, regional or a global scale.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…On the other hand, Steinberger et al (2017) more recently noted that establishing direct causal links between TPW and potential geodynamics triggers is far from straightforward, particularly because amounts of subduction are increasingly poorly constrained back in geological time. A recent study by Lin et al (2022) highlighted that using plate-kinematic reconstructions of the Pacific realm that incorporated intra-oceanic subduction zones (e.g., Chapter 1;Boschman et al, 2021) may provide very different models of the past geoid and mantle structure than those in which these subduction zones were not included. They demonstrated that geodynamic models that include intra-oceanic subduction provided a much better match with the present-day geoid, dynamic topography and mantle structure.…”
Section: Linking True Polar Wander and Mantle Dynamicsmentioning
confidence: 99%